Remote focused encoding and decoding of electric fields through acoustoelectric heterodyning - Jean L. Rintoul; Esra Neufeld; Chris Butler; Robin O. Cleveland; Nir Grossman (Communications Physics, 2023)
Abstract Heterodyning of signals through physical multiplication is the building block of numerous modern technologies. Yet, it has been mostly limited to the interaction between electromagnetic fields. Here, we report that heterodyning occurs also between acoustic and electric fields in liquid electrolytes. We predict acoustoelectric heterodyning via computational field modelling, which accounts for the vector nature of the electrolytic acoustoelectric interaction. We then experimentally validate the spatiotemporal characteristics of the field emerging from the acoustoelectric heterodyning effect. The electric field distribution generated by the applied fields can be controlled by the propagating acoustic field and the orientation of the applied electric field, enabling the focusing of the resulting electric field at remote locations. Finally, we demonstrate detection of multi-frequency ionic currents at a distant focal location via signal demodulation using pressure waves in electrolytic liquids. As such, acoustoelectric heterodyning could open possibilities in non-invasive biomedical and bioelectronics applications.